Collective action for water harvesting irrigation in the Lerma-Chapala Basin, Mexico - Scott, Christopher A.; Silva Ochoa, P. (Elsevier, 2002)
Water and watersheds are difficult to separate for management purposes. Providing irrigation as a supplement to rainfall for crop production requires considerable collective action at the watershed level to mobilize labor and other resources, as well as to make decisions and implement the distribution of benefits. Small-scale water harvesting irrigation systems in Mexico have endured for centuries. They now face considerable challenges with changes in the ejido property rights over land and water, the growing importance of alternative sources of livelihoods, and increasing scarcity and competition for water within the river basins.